Accounting Ethics Education: What and How To Teach? - Amelia Limijaya (Kajian Akuntansi, 2019)
For academics, accounting ethics education is a challenging field, not only because of the common perception that it is considered secondary to accounting technical courses, but also due to inconclusive results of its effectiveness on ethical behavior as well as uncertainty of what and how to teach. However, the recurring occurrence of accounting scandals as well support from accounting professional bodies on the importance of ethics in accounting curriculum, has contributed to the increasing attention given to accounting ethics. This paper tries to contribute to the growing accounting ethics literatures by reviewing the contents and learning methods. Eleven topic categories are suggested, along with fifteen learning methods which are inventoried from a number of literatures. Academics should try to discover interesting and unconventional methods to teaching ethics, to equip the traditional methods of teaching. It should be noted however, that the effectiveness of accounting ethics education does not rely only on having proper teaching materials and methods, but also on the institutional support and the learners’ commitment. Finally, three areas are identified to improve accounting ethics education, i.e. to develop a more principles-based approach, to shift the focus of ethics education to prevent ethical failures, as well as to take on a greater role of business ethics in general, including accounting ethics, to the society as a whole. Knowing the what and how aspects is expected to be a start in improving and fostering accounting ethics education.Keywords: accounting ethics education; teaching materials; teaching methods